Comparison of CAS and Manage Oauth in Single Sign on (SSO) Client Applications - Watini, Sri; Nursaputri, Pipit; Iqbal, Muhammad (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2020)
Single Sign On is one of the systems that have been developed long ago to meet the expectations of developers to provide ease and convenience of accessing data. In the development of the system, methods and protocols have been formed in varied ways to suit the needs of the developers . In a variety of methods and protocols , a developer can choose the architecture and protocols that can be used to develop the system. Central Authentication Service and Open authorization is two Single Sign On systems most widely used in the manufacture of a web log . Both can be used as the basis for the application of the system of Single Sign On for developers who intend to design a login system that is safe and comfortable , so that developers can create a system that suits his desire .